The Effect of Combined Therapy of Intranasal Desmopressin Spray and Sublingual Piroxicam in Patients with Acute Renal Colic (Annals of Medical Research, 2021)
None
Keywords: Desmopressin, Piroxicam, Acute Renal Colic